Biogas and bio-fertilizer production potential of abattoir waste as means of sustainable waste management option in Hawassa City, southern Ethiopia - T Sindibu; S.S. Solomon; D Ermias (Journal of Applied Sciences and Environmental Management, 2018)
The purpose of this study was to assess abattoir waste generation in Hawassa Municipality Abattoir (HMA) andits potential to produce biogas and bio-fertilizer employing a cross-sectional design and mathematical computation based on standard coefficients. The study demonstrated that HMA generates 885,881.6Kg of abattoir waste per year and using anaerobic digestion about 46,951.72m3/year of biogas can be produced. This waste has the potential of generating a total energy of 246,027.01KWh/year. The biogas or energy from the waste can replace the biomass (firewood and charcoal) and the expensive fossil fuels. Using the produced46, 951.72m3/year biogas could reduce the annual CO2 emission of 150,600.10Kg/kWh from kerosene, 150,600.10Kg/kWh from petrol, 132,882.50Kg/kWh from diesel or 132,882.50Kg/kWh from LPG use. The abattoir will be able to produce an estimated 65,112.3 Kg/year dry bio-fertilizer from biogas technology and this bio-fertilizer can be supplied to local farmers for crop production or can be used by city municipality for growing plants used for beautification. This obtainable bio- fertilizer is valued 29,951.66 USDper annum and to a certain extent will contribute to the reduction of domestic demand of chemical fertilizer thus will reduce the annual budget. As a long-term and sustainable waste management solution, installing anaerobic digestion plant is recommended, but using proper disposal method among the existing would serve as a short-term solution.